Enhancing the starting performance of elite swimmers through eight weeks of lateral entry training - Chen, C.; Gao, J.; Bacic, B.; Zhou, S. (Sports Biomechanics, 2025)
This study aims to explore the effects of 8 weeks of lateral entry training on the start performance of elite athletes and its impact on ordinary entry performance. Data were collected from 12 elite-level participants before and after the training using Kistler(9691A1) system with 3D force platform and high-speed cameras. 19 parameters of ordinary and lateral entry were assessed and analysed using paired samples t-tests. Compared to ordinary entry, the lateral entry performance was characterised by: decrease of both vertical force (5.77%) and maximum depth (6.09%) at a significance level (p < .01), and increase of flight distance (4.33%), first kick distance (3.90%) and push force (14.06%) at (p < .05). The results show that, compared to an ordinary entry technique, the lateral entry technique provides a 3.93%, 6.14%, and 8.29% reduction in time to reaching a 5 m, 10 m and 15 m distance (p = .01), showing performance improvements at start times. The 8-week training on the lateral entry technique did not have a significant impact on the time performance of the ordinary entry technique (p > .050). The findings presented herein offer pertinent insights for elite-level athletes, coaches and future investigations aimed at enhancing swimming start techniques and performance.